2019
DOI: 10.1002/slct.201902466
|View full text |Cite
|
Sign up to set email alerts
|

Central Composite Design To Optimize The Degradation Of Methylene Blue By Fenton Process

Abstract: Methylene blue (MB) is a cationic dye widely used in medicine as an antiseptic, also in other fields such as biology, chemistry, textile industry…etc. This pollutant exists in nature as the result of the fluid which is released from industries that can directly affect both the living organisms and the environment. This study consists of eliminating methylene blue by Fenton process under the influence of three parameters (pH,[FeII] and ratio R). The degradation of this substance was followed by a modeling of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Response surface methodology is an optimization technique consisting of various designs useful for optimizing the chemical reactions and industrial processes.In the present study, RSM was used to develop a mathematical relation between the response as a function of significant variables.With the aid of this mathematical relation, it is possible to predict experimental condition for obtaining any response. [39] The second-degree polynomial equation 6, obtained from RSM was useful for predicting the response as a function of independent variables.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Response surface methodology is an optimization technique consisting of various designs useful for optimizing the chemical reactions and industrial processes.In the present study, RSM was used to develop a mathematical relation between the response as a function of significant variables.With the aid of this mathematical relation, it is possible to predict experimental condition for obtaining any response. [39] The second-degree polynomial equation 6, obtained from RSM was useful for predicting the response as a function of independent variables.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Controlling pH is one of the most important aspects in electro-Fenton processes, because iron ions can precipitate and form iron hydroxides, limiting the efficiency of the process. However, numerous authors have shown that a pH value of 2 guarantees the solubility of iron ions in the system [51][52][53].…”
Section: Study Of the Activation Kinetics Of H 2 Omentioning
confidence: 99%
“…The ability of activated carbon to absorb MB, bromophenol blue, alizarine red-S, eriochrome black-T, malachite green, phenol red, and methyl violet from aqueous media was examined [13]. The elimination of MB with sulfonate-functionalized nano-porous silica spheres [14] and the removal of MB with jute ber carbon [15], carbon-doped graphitic carbon nitride [16], activated carbons [17], graphitic carbon nitride doped with the S-block metals [18], mesoporous carbon nitride [19], barium phosphate nano-ake [20], titania/gum tragacanth nanohydrogel [21], binary TiO 2 /reduced graphene oxide nanocomposite [22,23], diphenylanthrazoline compounds [24], soluble graphene nanosheets [25], graphene oxide/WO 3 nanorod composites [26], graphene oxide modi ed with Fe 3 O 4 nanoparticles [27], CdS nanostructures [28], and porous graphene wrapped SrTiO 3 nanocomposite [29] have been introduced earlier.…”
Section: Introductionmentioning
confidence: 99%